Metaphor and metonymy in word formation - Basilio, Margarida (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
This work investigates the relevance of analogy, metonymy and metaphor in word formation patterns and their products. Initially, the semantic side of proportional analogy in morphological restructuring is analyzed. The work then concentrates on the role of metonymy in the formation of instrumentals and agent nouns. The last part of the work is dedicated to the role metaphor in compounding. The main point of the paper is to show how metaphor in fundamental to the constitution of the lexicon and, consequently, how unfortunate for the discussion of metaphor in language is the relative disregard to word-formation processes.